Rapid determination of sildenafil and its analogues in dietary supplements using gas chromatography–triple quadrupole mass spectrometry - Mokhtar, Siti Umairah; Chin, S. -T.; Kee, C. L.; Low, M. Y. (Elsevier Ltd., 2016)
Application of gas chromatography–triple quadrupole mass spectrometry for identification, confir-mation and quantification of 6 phosphodiesterase-5 (PDE-5) inhibitors (sildenafil, dimethylsildenafil,homosildenafil, thiosildenafil, thiodimethylsildenafil and thiohomosildenafil) in dietary supplementswas investigated. The MS was operated in multiple reaction monitoring mode, for better sensitivity andselectivity. In this manner, the method is adequate to reduce background noise with less interference fromco-eluting compounds in the samples. Two different ionisation techniques, electron ionisation (EI) andchemical ionisation (CI), were studied and compared. The chromatographic separation was performedon a short 10 m non-polar capillary column without any derivatisation step. This permitted fast analysisfor all analogues with retention time less than 11 min, for both techniques. Use of backflushing can aidmethod retention time reduction and improves column maintenance. Evaluation of method validationincluded limit of detection (LOD), lower limit of quantitation (LLOQ), linearity, precision and recoverywere performed for both EI and CI techniques. The LOD obtained varied from 0.03 to 1.50 _g/g and theLLOQ ranged from 0.10 to 5.00 _g/g. Good calibration linearity was obtained for all analogues for bothtechniques, with correlation coefficients (r2) higher than 0.99. Mean recoveries of all analogues usingCI show higher values (83.4–108.8%) than that of EI (61.9–91.1%). The intra- and inter-assay precisionswere evaluated for all analogues at spiked concentration of 10 _g/g and the relative standard deviationwas less than 15% for both methods. These methods were then successfully applied to dietary supple-ment samples without prior derivatisation, confirming that the samples were adulterated with sildenafiland/or its analogues.